Barking up the wrong tree: the dangers of taxonomic misidentification in molecular phylogenetic studies - de Almeida, Rafael Felipe; Pellegrini, Marco O.O.; de Morais, Isa L.; Simão-Bianchini, Rosangela; Rattanakrajang, Pantamith; Cheek, Martin; Simões, Ana Rita G. (Plant ecology and evolution, 2023)
Background and aims – Keraunea is a Brazilian endemic genus that has sat uncomfortably in Convolvulaceae where it was placed due to an enlarged and adnate fruit bract typical of Neuropeltis . A recent molecular phylogeny suggested that two of its five morphologically almost identical species actually belong to two different families, Malpighiaceae (superrosids) and Ehretiaceae (superasterids). Later studies have demonstrated that Keraunea effectively belongs to Ehretiaceae, but the proposal of one species belonging to Malpighiaceae has remained problematic. In this study, we re-assess this hypothesis, discuss the issues that have led to this assumption, and offer insights on the importance of carefully using herbarium collections and incorporating morphological evidence in systematic studies. Material and methods – Sequences of matK , rbcL , and ITS for all 77 currently accepted genera of Malpighiaceae, K. brasiliensis and Elatinaceae (outgroup) were compiled from GenBank and analysed with Maximum Likelihood and Bayesian Inference criteria for nuclear, plastid and combined datasets. Additional database and herbarium studies were performed to locate and analyse all duplicates of the holotype of K. brasiliensis to check for misidentified or contaminated material. Key results – Our examination of expanded DNA datasets and herbarium sheets of all K. brasiliensis isotypes revealed that a mistake in tissue sampling was, in fact, what led to this species being proposed to belong in Malpighiaceae. Kew’s isotype had a leaf of Malpighiaceae (likely Mascagnia cordifolia ) stored in the fragment capsule, which was sampled and sequenced instead of the actual leaves of K. brasiliensis . Recently published studies have settled the placement of Keraunea in Ehretiaceae (Boraginales) and proposed three additional species. Conclusions – DNA sequences can be helpful in classifying taxa when morphology is conflicting or of a doubtful interpretation, with molecular phylogenetic placement being established as a popular tool accelerating the discovery of systematic relationships. Nonetheless, molecular techniques are also susceptible to methodological mistakes, which necessitates building a solid foundation of plant morphology and taxonomy to avoid artefacts in phylogenetic studies.